Identificação e caracterização de elementos retrotransponíveis da família Rex do genoma de espécies do genêro Leporinus SPIX, 1829 (Teleostei: Anostomidae) - Borba, Rafael Splendore de [UNESP] (2013)
The Anostomidae family is an interesting model for repetitive elements studies, mainly due the presence of high number of heterochromatic segments related to a peculiar system of female heterogamety, which is restricted to a few species belonging to the Leporinus genus. In this way we performed a cytogenetic mapping of retrotransposable elements Rex1, Rex3 and Rex6 in chromosomes of Leporinus: L. elongatus, L. macrocephalus and L. obtusidens, which have sex chromosomes system, and L. friderici, L. lacustris and L. striatus, in order to increase the knowledge of the genomic organization of the genus, observe if these elements are related to heterochromatic regions and whether its distribution is compatible with the hypothesis of a stable macrostructure kept in the karyotype of the genus. Amplification and sequencing of the elements Rex1 and Rex3 showed different compositions regarding the number of base pairs of these elements for these species, but the Rex6 element has not been identified in genome of the species studied. The FISH technique using Rex1 element as probe resulted different distribution pattern: Leporinus elongatus, L. macrocephalus and L. obtusidens presented clusters isolated in the terminal region and the others species present signals disperse in all chromosomes and some signals on terminal position. The Rex3 signals are accumulated mainly in terminal position in all chromosomes for all species. The W chromosome of L. elongatus, L. macrocephalus and L. obtusidens, presents Rex3 signal on interstitial position. Some variations were observed regarding the hybridization signals among species. These results suggest the occurrence of different levels of activity of these elements during the evolutive process of the species analyzed. Despite the quite conserved karyotypic macrostructure of Leporinus species, through our results was possible to observe some variation on hybridization signals pattern, specially among the group...